The Role of Islamic Religious Education in Shaping the Character of Elementary School Students in the Digital Era: A Case Study at SDN 010 Bontang Utara - Nurully Kesuma Ningrum; St. Nurhayati Ali; Dadang Sumarna; Muhammad Naim; Nasir. S (CV. Edujavare Publishing, 2026)
The rapid advancement of digital technology has the potential to erode the character and morality of elementary school students through exposure to negative content on social media, particularly when not counterbalanced by a strong foundation of Islamic Religious Education (IRE). This study aims to analyze the role of IRE in shaping students' character, to identify shifts in student character in the digital era, and to explore students' experiences in participating in IRE learning at SDN 010 Bontang Utara. This study employs a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews with the principal, IRE teachers, homeroom teachers, students, parents, education staff, and the school committee, and documentation study. Data were analyzed through data reduction, data display, and conclusion drawing, with trustworthiness established through credibility, transferability, dependability, and confirmability. The results indicate that IRE at SDN 010 Bontang Utara has contributed meaningfully to instilling values of honesty, responsibility, patience, empathy, and humility through methods adapted to grade levels, ranging from habituation and modelling in lower grades to reflective-dialogical approaches in upper grades. However, its effectiveness is still constrained by intense exposure to negative digital content, which triggers character shifts such as the use of coarse language, declining manners, and digital bullying, particularly among upper-grade students. Students' learning experiences of IRE are generally positive, yet a gap remains between instructional content and the digital realities students face daily. This study recommends strengthening a more contextual, adaptive, and digitally literate approach to IRE grounded in Islamic values, alongside closer synergy among teachers, parents, and the school ecosystem as a moral safeguard for the digital generation.